Cross-Cutting Themes in Employment Experiences During the Crisis. (Policy Papers; Policy Paper ;, 2010)
The human cost of the recent global crisis is reflected in its impact on the labor market. Explaining why economies with similar downturns had very different employment trends can help design policies to reduce such costs and improve labor markets. This paper analyzes the recent employment experiences of six economies: Germany, Korea, Mexico, New Zealand, Spain, and Sweden. These economies represent a wide range of labor market institutions, policy responses, and outcomes to the crisis. The divergence of labor market outcomes and of the effectiveness of policies during the crisis can be explained by the interaction between the nature of the shocks and differences in the structure and institutions of each country's economy. The worst job losses compared to the drop in output followed permanent shocks, particularly in dual labor markets and in the presence of wage rigidities. Policies to avoid job cuts were much more effective when they were well-targeted and responded to temporary shocks. In contrast, policies to facilitate labor movements were more appropriate following permanent shocks.